Frequency of glucose‐6‐phosphate dehydrogenase–deficient red blood cell units in a metropolitan transfusion service. Issue 3 (28th June 2012) - Francis, Richard O.; Jhang, Jeffrey; Hendrickson, Jeanne E.; Zimring, James C.; Hod, Eldad A.; Spitalnik, Steven L.
<x xml:space="preserve">Abstract</x> BACKGROUND: Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is characterized by red blood cell (RBC) destruction in response to oxidative stress. Although blood donors are not routinely screened for G6PD deficiency, the transfusion of stored G6PD‐deficient RBCs may have serious adverse outcomes. By measuring G6PD enzyme activity of RBC units from a large metropolitan hospital transfusion service, we sought to determine 1) the prevalence of G6PD‐deficient RBC units, 2) if G6PD activity changes during storage, and 3) if G6PD activity in segments correlates with its activity in the bags. STUDY DESIGN AND METHODS: Quantitative G6PD activity was measured in 301 randomly selected RBC units and 73 D+C−E− (i.e., R0r or R0R0) RBC units, all stored in additive solutions. G6PD deficiency was defined as activity less than 60% of the normal mean. RESULTS: The frequency of G6PD‐deficient units in the general inventory was 0.3% (1/301; 95% confidence interval [CI], <0.01%‐2.1%). In contrast, its frequency in D+C−E− RBC units was 12.3% (9/73; 95% CI, 6.4%‐22.0%). G6PD activity did not significantly change during the 42‐day storage period, and G6PD activity measured in RBC storage bags and attached segments correlated well (r = 0.7‐0.9, p ≤ 0.001, Spearman rank correlation). CONCLUSIONS: Although the frequency of G6PD‐deficient RBC units in the transfusion service general inventory was relatively low, it was significantly higher among a subset of R0r or R0R0 units. The latter are preferentially allocated for transfusion to patients with sickle cell disease to decrease the risk of RBC alloimmunization, possibly allowing more of these units to be inadvertently targeted to these patients.